Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1007/s12035-021-02458-y
|View full text |Cite
|
Sign up to set email alerts
|

MiR-135-5p Alleviates Bone Cancer Pain by Regulating Astrocyte-Mediated Neuroinflammation in Spinal Cord through JAK2/STAT3 Signaling Pathway

Abstract: Bone cancer pain (BCP) was associated with microRNA dysregulation. In this study, we intended to clarify the potential role of miR-135-5p in a BCP mouse model, which was established by tumor cell implantation (TCI) in the medullary cavity of the mouse femur. The BCP related behaviors were tested, including the paw withdrawal mechanical threshold (PWMT) and number of spontaneous flinches (NSF). The miRNA expression profiles in astrocytes of the sham and tumor groups were compared, and miRNA microarray and quant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…Some experiments have demonstrated that the proliferative capacity of astrocytes intervened by AG490 or with STAT3 defects is reduced to a certain extent ( Washburn and Neary, 2006 ; Sarafian et al, 2010 ). Liu et al (2021) demonstrated that not only were the activation levels of JAK2 and STAT3 significantly reduced by miR-135-5p mimics intervention but also GFAP, IL-1β, and TNF-α expression, which was consistently decreased. Moreover, functional in vitro studies have also confirmed that miR-135-5p potentially inhibits the JAK2-STAT3 signaling pathway in bone cancer pain, and histological staining has proven that miR-135-5p can directly interrupt the activity process of JAK2 and its upstream and downstream molecules in astrocytes ( Liu et al, 2021 ).…”
Section: Key Signaling Mechanisms and Molecules Regulating Reactive A...mentioning
confidence: 92%
See 1 more Smart Citation
“…Some experiments have demonstrated that the proliferative capacity of astrocytes intervened by AG490 or with STAT3 defects is reduced to a certain extent ( Washburn and Neary, 2006 ; Sarafian et al, 2010 ). Liu et al (2021) demonstrated that not only were the activation levels of JAK2 and STAT3 significantly reduced by miR-135-5p mimics intervention but also GFAP, IL-1β, and TNF-α expression, which was consistently decreased. Moreover, functional in vitro studies have also confirmed that miR-135-5p potentially inhibits the JAK2-STAT3 signaling pathway in bone cancer pain, and histological staining has proven that miR-135-5p can directly interrupt the activity process of JAK2 and its upstream and downstream molecules in astrocytes ( Liu et al, 2021 ).…”
Section: Key Signaling Mechanisms and Molecules Regulating Reactive A...mentioning
confidence: 92%
“… Liu et al (2021) demonstrated that not only were the activation levels of JAK2 and STAT3 significantly reduced by miR-135-5p mimics intervention but also GFAP, IL-1β, and TNF-α expression, which was consistently decreased. Moreover, functional in vitro studies have also confirmed that miR-135-5p potentially inhibits the JAK2-STAT3 signaling pathway in bone cancer pain, and histological staining has proven that miR-135-5p can directly interrupt the activity process of JAK2 and its upstream and downstream molecules in astrocytes ( Liu et al, 2021 ). These studies demonstrate that JAK-STAT3 signaling has a key contribution in the occurrence and progression of neuropathic pain via the modulation of astrocyte activation.…”
Section: Key Signaling Mechanisms and Molecules Regulating Reactive A...mentioning
confidence: 92%
“…In addition, miR-34c-5p has recently been identified in DRG neurons as pronociceptive by regulating the transcription of Cav2.3 , P2rx6 , Oprd1 , and Oprm1 [ 84 ]. In the spinal cord, following the induction of various models of cancer-induced pain, imbalances on the levels of miRNAs have been found: down-regulation of miR-124, which negatively regulated synaptopodin ( Synpo ), a key component in synaptic transmission [ 65 ]; up-regulation of miRNA-330, which seems to modulate the expression of GABA B R2 [ 83 ]; and decreases in miR-135-5p, which regulated JAKs/Stat3 signalling, in spinal astrocytes [ 70 ]. Furthermore, changes in miRNAs have also been associated with certain drug-induced pain disorders, such as that induced by the use of oxaliplatin to treat advanced colorectal cancer [ 150 ].…”
Section: Non-coding Rnas and Painmentioning
confidence: 99%
“…However, microarrays use already known sequences, thus making them unsuitable for the discovery of novel ncRNAs. Nonetheless, microarray-based methods can be used as cost-effective procedures to validate the presence of ncRNA from a known or predicted transcript and have proven useful in pain research [ 66 , 70 ].…”
Section: Non-coding Rnas and Painmentioning
confidence: 99%
“…JAK2/STAT3 pathway is implicated in inflammatory pain, 11 neuropathic pain, 12 and BCP. 13 NLRP3 inflammasome is also involved in the development and progression of BCP. 14 , 15 In addition, the activation of NLRP3 inflammasome is inhibited after the suppression of JAK2/STAT3 pathway.…”
Section: Introductionmentioning
confidence: 99%